2015
DOI: 10.1021/acsphotonics.5b00626
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Role of Shape, Ligands, and Dielectric Constants in the Absorption Properties of Colloidal CdSe/CdS Nanocrystals

Abstract: We calculated the absorption coefficient of colloidal wurtzite CdSe/CdS nanocrystals (NCs), ranging from spherical to strongly elongated shapes (aspect ratio up to 21) by correlating the NC absorbance spectrum to the NC elemental composition and overall dimensions. We compared experimental data with numerical finite-element calculations of the NC absorption coefficient, which can account for the nonspheroidal NC shape and the influence of the organic ligand shell. The results unveiled that quantum confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…In the case of non-analytical shapes such as our CdSe/CdS DiRs that are composed of a CdSe core located near one end of an elongated CdS shell, numerical models are required to evaluate the dielectric screening. 18 We performed 3D finite element numerical simulations (COMSOL multiphysics) to examine the near field optical properties of hNCs and calculate the electric field inside the CdSe core. The simulation domain comprised a spherical volume representing a CdSe/CdS DiR embedded in chloroform.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of non-analytical shapes such as our CdSe/CdS DiRs that are composed of a CdSe core located near one end of an elongated CdS shell, numerical models are required to evaluate the dielectric screening. 18 We performed 3D finite element numerical simulations (COMSOL multiphysics) to examine the near field optical properties of hNCs and calculate the electric field inside the CdSe core. The simulation domain comprised a spherical volume representing a CdSe/CdS DiR embedded in chloroform.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
“…Values were taken from bulk data at the respective band edges (1.75 eV for CdSe, 21 2.42 eV for CdS 22 ), with the imaginary part of both set to zero, as we can assume ε imag ≪ ε real near the band edge, 23 and applying a reduction of 15% due to residual quantum confinement effects. 18,24 We previously found that the dielectric function in CdSe/CdS hNCs is somewhat reduced compared to bulk at 4.2 eV. 18 Since bulk ε real is nearly flat in the energy range between 4.2 eV and the band edge, 24 we applied the same 15% reduction to the CdS and CdSe optical constants at the band edge.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefit of this particle is the higher specific absorption coefficient in relation to spherical particles of the same material as Angeloni et al. proved by their work . As a reference material CdSe/CdS nanorods are chosen.…”
Section: Introductionmentioning
confidence: 99%